Automation of the Photobioreactor Lighting System to Manage Light Distribution in Microalgae Cultures - Beata Brzychczyk; Jan Giełżecki; Krzysztof Kijanowski; Tomasz Hebda; Filip Rzepka (Energies, 2023)
Automation of the lighting system for phototrophiccultures in photobioreactors is a process of automation and control of lighting inside. Photosynthetic microorganisms, in order to develop and grow, require a species-specific type of visible light radiation. The automation of the lighting system was based on the industrial PLC Modicon TM221C24T controller according to the submitted and received patent No. 242154. The system was integrated with a quantum sensor, which allows for setting the colour of light and controlling the intensity and exposure time based on protocols set by the operator. The data obtained from the PAR photosynthetically active radiation sensor make it possible to adjust the distribution of light to the actual needs of the culture’s radiant energy. The unit also allows for remote control of multiculture farms. It allows you to simulate sunrise and sunset using the astronomical clock function set for a given species of microalgae. Ultimately, the work was undertaken on the implementation and use of a system for measuring the light spectrum at each point of the bioreactor using a fibre-optic immersion probe.